Do Geographic Effects Matter? A Literature Review - Li, Chengcheng; Wang, Xiaoqiong (International Journal of Economics and Financial Issues, 2018)
This paper provides a broad review of studies on geographic effects. Geographic effects have both corporate finance and asset pricing implications. A wide range of geographic effects topics are summarized in this study, including board structure, investment decisions, payout policy, innovation, mergers and acquisitions, lending and borrowing, and pricing discrimination. This paper provides a connection of geographic effects with two basic corporate finance issues: information asymmetry and agency problems. Keywords: Geographic Proximity, Information Asymmetry, Agency Problem, Corporate Decisions, Lending and Borrowing, Pricing Discrimination JEL Classifications: G30, G38, G20